(untitled) (University Journal of Zoology, Rajshahi University, 2012)
The study was conducted to investigate the incidence of gastrointestinal parasites of buffalo in different slaughter houses of Chittagong Metropolitan Area, Bangladesh. A total of 100 faecal samples were collected from three slaughter houses and studied by coproscopic examinations. Direct smear, sedimentation and floatation techniques along with egg micrometry were conducted to identify various parasitic eggs. Among 100 faecal samples 69% were positive for different individual parasitic infestation. Trematodes, nematodes, cestodes and protozoan infestations were 48%, 16%, 2% and 3%, respectively. Among the trematodes Schistosoma sp. (23%), Paramphistomum sp. (15%) and Fasciola sp. (10%) were found. Incidence of nematode infestations were Toxocara sp (4%), Oesophagostomum sp. (5%), Cooperia sp. (2%), Bunostomum sp. (3%) and 1% for both Trihostrongylus sp. and Strongyloides sp. Mixed infection were observed 7% of positive samples. Results indicate that the heavy worm burden in buffaloes causes severe economic loss to the farmers by reducing the overall productivity. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10703 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 05-07